2016
DOI: 10.1038/srep22666
|View full text |Cite
|
Sign up to set email alerts
|

Stalking influenza by vaccination with pre-fusion headless HA mini-stem

Abstract: Inaccuracies in prediction of circulating viral strain genotypes and the possibility of novel reassortants causing a pandemic outbreak necessitate the development of an anti-influenza vaccine with increased breadth of protection and potential for rapid production and deployment. The hemagglutinin (HA) stem is a promising target for universal influenza vaccine as stem-specific antibodies have the potential to be broadly cross-reactive towards different HA subtypes. Here, we report the design of a bacterially ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
109
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(122 citation statements)
references
References 38 publications
2
109
2
Order By: Relevance
“…Besides the mini-HA and VRC headless HA constructs, other stem-based immunogens have been designed and reported 64, 65, 66, 67, 68, 69 . Another proposed approach to elicit heterologous and heterosubtypic immunity to the HA stem was the use of HA chimeras, where head domains from different subtypes are fused with a single stem domain, to direct the antibody response to the conserved stem region by sequential immunization with different chimeras 70, 71 .…”
Section: Design Of a More Universal Vaccinementioning
confidence: 99%
“…Besides the mini-HA and VRC headless HA constructs, other stem-based immunogens have been designed and reported 64, 65, 66, 67, 68, 69 . Another proposed approach to elicit heterologous and heterosubtypic immunity to the HA stem was the use of HA chimeras, where head domains from different subtypes are fused with a single stem domain, to direct the antibody response to the conserved stem region by sequential immunization with different chimeras 70, 71 .…”
Section: Design Of a More Universal Vaccinementioning
confidence: 99%
“…Immunized mice exhibited high levels of cross-reactive antibodies against multiple HA subtypes and were protected against lethal challenge with A/PR/8/34 (H1N1)[32]. In a subsequent study, a similar HA2-based subunit vaccine was found to be highly immunogenic in mice conferring protection against lethal challenge with A/Hong Kong/68 (H3N2)[33]. Mallajosyula et al developed a headless HA stem vaccine based on the group 1 A/PR8 virus[34].…”
Section: Vaccine Approaches Targeting the Ha Stem Regionmentioning
confidence: 99%
“…Bommakanti et al [49] reported that a headless H1 HA construct produced in E. coli elicited protection in mice against a heterologous H1 virus, but not heterosubtypic virus. Two follow up studies by the same group reported an improved headless H1 HA construct that elicited 30% cross-H3 protection in mice [50]; and a prefusion mini headless H5 HA construct that elicited the protection against lethal challenge of H5 and H1 (group 1) and H3 (group 2) viruses [51]. A recent study by Lu et al [52] reported a multi-step rational design approach that resulted in the headless HA displays correctly folded conserved conformational epitopes, but with no report on its in vivo efficacy.…”
Section: Stem-based Vaccine Design That Aims To Elicit Cross-subtype mentioning
confidence: 99%